MANAGEMENT OF DIGITAL KITAB KUNING LEARNING AT THE AL-MANHAJ TRAINING INSTITUTE - Sri Wahyuni; Taftinatul Ilmiah; Fahma Hurrosatud Diyanah; Fadiah Alfi Laila; Yusrolana Yusrolana (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2026)
The development of digital technology has transformed nonformal education, including kitab kuning learning that was previously associated with conventional systems. This condition requires course institutions to manage learning and organizational processes in a digital-based and adaptive manner. This study aims to describe the management of digital-based kitab kuning learning at Al-Manhaj Course Institution, covering the implementation of vision and mission, class grouping and learning management, organizational structure, learning media and challenges, as well as learning evaluation and quality assurance. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, documentation, and observation. Data analysis consisted of data reduction, data display, and conclusion drawing. The findings show that Al-Manhaj provides accessible digital-based kitab kuning learning through staged class grouping in the Marhalah, Mutafahim, and Mufaqqih programs, supported by teacher management based on POAC principles. The institution applies a clear organizational structure aligned with management functions. Digital media support learning activities despite technical and time-related challenges. Learning evaluation is conducted continuously through formative and summative assessments and digital-based student feedback to ensure learning quality.